INDEPENDENSI AUDITOR SEBAGAI PEMEDIASI PENGARUH AUDIT FEE DAN TIME BUDGET PRESSURE PADA KUALITAS AUDIT - Santhi, Merta Widya; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi; Vol 19 No 3 (2017), 2017)
Auditor has ability provide audit report if the auditor able to maintain independence. The aim of this research is to know and prove the effect of audit fee,  time budget pressure on auditor independence. The effect of audit fee, time budget pressure, independence of auditors on audit quality. The effect of audit fee, time budget pressure on audit quality through the auditor's independence. Research using saturated sampling technique using path analysis. The results this analysis are audit fee and time budget pressure ha s negative effect on the independence of auditors. Audit fees and time budget pressure ha s negative effect on the audit quality. The auditor's independence has positive effect on audit quality. If the independence of the auditor is affected by both of audit fee and time budget pressure this will affect the audit quality.
Keywords: audit fees, time budget pressure, auditor independence, audit quality.